Development of a New Referral Tool to Identify Psoriasis Patients with Concomitant Psoriatic Arthritis: Results of the Prospective DAPPER Cohort - Tamara W. van Hal; Michelle L.M. Mulder; Mark H. Wenink; Frank H.J. van den Hoogen; Jake S.F. Maurits; Marcel C. Pasch; Juul M.P.A. van den Reek; Elke M.G.J. de Jong (Medical Journals Sweden, 2023)
Patients with psoriasis are at risk of developing psoriatic arthritis, which can lead to joint damage. While screening questionnaires have been developed, their performance varies. The objective of this study was to develop a referral tool for dermatologists to identify psoriasis patients with concomitant psoriatic arthritis for rheumatological referral. This study used data from the DAPPER study, in which psoriasis patients were screened by a rheumatologist for the presence of concomitant psoriatic arthritis. Multivariable regression analysis was used to identify predictive variables for the presence of concomitant psoriatic arthritis: treatment history with conventional systemic drugs (odds ratio (OR) 2.97, 95% confidence interval (95% CI) 1.01-8.74, p = 0.04), treatment history with biologicals/small molecule inhibitors (OR 2.90, 95% CI 1.52-5.53, p = 0.01), patient-reported history of joint pain not caused by trauma (OR 4.23, 95% CI 1.21-14.79, p = 0.01), patient-reported history of swollen joints (OR 4.25, 95% CI 2.17-8.32, p < 0.001), and patient-reported history of sausage-like swollen digits (OR 2.38, 95% CI 1.25-4.55, p = 0.01). Based on these variables, a referral tool was created with an area under the curve of 0.82. This referral tool could be used to aid dermatologists to identify psoriasis patients with concomitant psoriatic arthritis, who may benefit from rheumatological referral.